Effects of oxygen supplementation in ewes subjected to laparoscopic ovum pick-up under total intravenous anesthesia - Silva, Maria Fernanda Santos (2023)
Laparoscopy procedures are useful tools to perform some assisted reproductive biotechnologies in ewes, it requires general anesthesia and manoeuvres that might result in alteration of the cardiopulmonary function. For this reason, this study aimed to investigate the effects of oxygen supplementation as a therapeutic measure to mitigate these alterations in ewes submitted to laparoscopic ovum pick-up (LOPU) under total intravenous anesthesia (TIVA). Twenty-four healthy adult ewes were submitted to two LOPUs with a 21 days interval, under ketamine-midazolam anesthesia, and receiving each of the two experimental in random order, oxygen treatment (OT) 50 mL/kg/min of oxygen via endotracheal tube and control treatment (CT) not receive any inhalation treatment. Heart rate (HR), respiratory rate (fR), peripheral oxygen saturation (SpO2), mean arterial pressure (MAP), rectal temperature (RT), end-tidal CO2 concentration (EtCO2) and recovery anesthesia time were evaluated during LOPU, arterial blood gases and electrolytes were evaluated after induction of anesthesia and at the end of the LOPU. Variables were compared between groups and moments using ANOVA. MAP, SpO2, PaO2, SaO2 and pH were higher in OT, while EtCO2, PaCO2, temperature loss and recovery time were lower. These results allow to conclude that oxygen supplementation in ewes submitted to LOPU under TIVA provides benefits in order to mitigate physiological alterations.